Peran Orang Tua Dalam Membentuk Karakter Disiplin Pada Anak Dalam Penggunaan Gadget: Studi Pada Masyarakat di Lingkungan RT.04 RW.13 Kelurahan Palangka, Kecamatan Jekan Raya Kota Palangka Raya - Asmina Bualiku; Eli Karliani; Ahmad Saefulloh (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This research was conducted to find out the role of parents in shaping the character of discipline in children in using gadgets and to describe and analyze the positive and negative impacts of using gadgets for children aged 5-11 years in the neighborhood of RT.04 RW.13 Palangka Village, Jekan Raya District, Palangkaraya City. This research approach uses a qualitative approach that seeks to describe the role of parents in forming the character of discipline in children in the RT.04 RW.13 Palangka Village, Jekan Raya District, Palangka Raya City. This research was conducted to find out the role of parents in shaping the character of discipline in children in using gadgets and how positive and negative impacts children have in using gadgets in the RT.04 RW.13 Palangka Village, Jekan Raya District, Palangka Raya City. In this study, data collection techniques were carried out purposively and accidental sampling. Purposive is a sampling technique with certain considerations. Accidental sampling is a way to determine the number of samples in accordance with the size of the sample that will be used as the actual data source. The purposive was 7 people with accidental sampling totaling 64 families. Based on the results of the research that has been done, it can be concluded: (1) The role of parents, such as in forming the character of discipline in children in using gadgets, is that parents must provide strict rules, provide a good understanding of the use of gadgets, supervise the use of gadgets in children, provide a good example for children in using gadgets, Diverting children's attention so they don't play gadgets too often, Provide alternative games, also provide limits on the use of gadgets and provide wise explanations to children so they don't depend too much on gadgets. (2) one of the positive impacts of using gadgets on children aged 5-11 years is that they can increase children's knowledge, (3) one of the negative effects of using gadgets on children aged 5-11 years is that children become lazy, lack of enthusiasm and have health problems